2018
DOI: 10.3390/geosciences8040128
|View full text |Cite
|
Sign up to set email alerts
|

Basin Resonance and Seismic Hazard in Jakarta, Indonesia

Abstract: Abstract:We use earthquake ground motion modelling via Ground Motion Prediction Equations (GMPEs) and numerical simulation of seismic waves to consider the effects of site amplification and basin resonance in Jakarta, the capital city of Indonesia. While spectral accelerations at short periods are sensitive to near-surface conditions (i.e., V S30 , average shear-wave velocity at topmost 30 m of soil), our results suggest that, for basins as deep as Jakarta's, available GMPEs cannot be relied on to accurately e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Although the contrast between Holocene and Pleistocene deposits is small and their boundary is not well resolved in our V s ahs map, their deposits obviously fill the Jakarta basin to a depth of at least 150 m. These deposits reach the outer part of the Jakarta administrative margin mostly to the southwest, more than 10 km away. The result is in accordance with Cipta et al [20] who reported the estimation of the basin extension based on extrapolation of the basement depth. The higher V s ahs found in the southern part of the basin may relate to Tertiary volcanic deposits, or even the edges of the basin, which is Tertiary rock.…”
Section: Correlation With Surface Geologysupporting
confidence: 92%
See 3 more Smart Citations
“…Although the contrast between Holocene and Pleistocene deposits is small and their boundary is not well resolved in our V s ahs map, their deposits obviously fill the Jakarta basin to a depth of at least 150 m. These deposits reach the outer part of the Jakarta administrative margin mostly to the southwest, more than 10 km away. The result is in accordance with Cipta et al [20] who reported the estimation of the basin extension based on extrapolation of the basement depth. The higher V s ahs found in the southern part of the basin may relate to Tertiary volcanic deposits, or even the edges of the basin, which is Tertiary rock.…”
Section: Correlation With Surface Geologysupporting
confidence: 92%
“…In further studies, it might be useful to investigate the frequency-dependence of body-wave polarization in an attempt to reveal further details of the shallow V s profiles. Our estimates of V s ahs reflect the shallow Vs structure obtained within the Jakarta city limits in earlier studies [15,16], but extended this information beyond the city limits of Jakarta to what is thought to be the basin edge [20]. Although the surface geology of the entire study area is composed of quaternary sediments (Figure 1b), we found that on average, V s ahs increases towards the outer edge of the study area ( Figure 6).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Cipta et al (2018) have used 2-D waveform modelling along an NS cross-section of the Jakarta Basin model developed here to show that very large amplification of ground motion (up to 1500 per cent PGV) can occur for a large scenario earthquake on the Java Trench, with the thicker sediments in the north experiencing the largest amplification. However, the wedged shape of the basin edge as it shallows to the south also plays an important role in amplifying seismic waves (up to 1200 per cent PGV), particularly for the intraslab earthquake scenario considered by Cipta et al (2018). For both the megathrust and intralsab scenarios, the spectral amplifications were most prominent in the period range 5-7 s, similar to that of the observed f l 0 HVSR peaks.…”
Section: Sharp F Lmentioning
confidence: 99%